Bodies and bureaucracy: The demise of the body snatchers in 19th century Britain. Issue 4 (11th October 2021) - Philp, Janet
Abstract: As European anatomical teaching developed in the middle ages, anatomists found themselves balanced between the educational and judicial systems. Dissection was associated with the final stages of legal prosecutions and the supply of bodies was severely limited. Driven by increasing student demand for dissection, anatomists found themselves pushed to explore alternative routes for body supply. This led to association with the developing profession of grave robber, body snatchers, and even murderers. Keen to protect themselves from increasing vulnerability to legal prosecution, the eminent anatomists of the United Kingdom pushed for government legislation to provide a supply of cadaveric material for education. This article looks at the development of the Anatomy legislation in the United Kingdom in 1832. By highlighting three events in the early 1800s, it demonstrates that the development of the legislation was for addressing the concerns of the anatomists rather than any ethical concerns about the cadaveric supply. The poorest in society were used to develop the medical understanding of the more wealthy before, during, and after the introduction of the legislation. The first event made the anatomists criminal liable for body supply while the latter two events linked anatomists with murderers. The increasing demand for legislation to provide a supply of cadaveric material released the anatomists from the financial burden of dealing with grave robbers while still allowing dissection tables to be supplied with the poorest in society.